Faktor Faktor Yang Mempengaruhi Struktur Modal - Darno, Darno; Maryono, Maryono (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Capital is the main problem for business actors or companies. Companies need additional capital to develop products so they can compete with other similar companies. This research aims to analyze what factors influence the capital structure of manufacturing companies listed on the IDX for the 2020-2022 period. This research uses a pecking order theory and trade-off theory approach to build arguments between the independent variable and the dependent variable. The sample obtained from the purposive sampling technique was 42 companies over 4 years (126 observation data). The data analysis technique uses multiple linear regression analysis. The research results prove that company size has a significant negative influence on capital structure so that the hypothesis is rejected, as well as what happens to profitability on capital structure which also rejects the hypothesis, namely that profitability has a negative and insignificant effect. However, the results of the relationship between asset structure and capital structure have a significant positive influence so that the hypothesis is accepted. The coefficient of determination value proves that it is concluded that 18.3% of the independent variables, namely company size, asset structure and profitability in this study, can influence the dependent variable, namely capital structure, while 81.7% can be explained outside the variables in this study.